THE IMPACT OF PRODUCT QUALITY, BRAND IMAGE AND PRICE ON CUSTOMER SATISFACTION OF OOTD SERVICE DISTRICT SEMPU BANYUWANGI - Dilla Cattleyana Sab; Yeni Eka Safitri (Jurnal Ekonomi, 2022)
UMKM OOTD Supply (Outfit Of The Day) is a business engaged in the fashion sector. This study examines the effect of product quality, brand image, and price variables on customer satisfaction either partially or simultaneously. The sample in this study amounted to 140 respondents who are OOTD Supply UMKM customers—collecting data in this study using observation, interviews, distributing questionnaires and documentation. The questionnaire used a 5-point Likert scale to measure 14 questions—data processing in this study used SPSS 25 with a random sampling technique using the Roscoe formula. The results of this study indicate that the influence of product quality, brand image, and price simultaneously has a positive and significant effect on customer satisfaction at OOTD Supply. So in this study, product quality is the dominant variable affecting customer satisfaction based on comparing the tcount values of the three variables.